When and where do elections matter? A global test of the democratization by elections hypothesis, 1900–2010. Issue 3 (3rd April 2018) - Edgell, Amanda B.; Mechkova, Valeriya; Altman, David; Bernhard, Michael; Lindberg, Staffan I.
ABSTRACT: Successive multiparty elections in sub-Saharan Africa are associated with incremental democratization. Yet tests in other regions are less than encouraging. Non-significant findings on Latin America and post-communist Eurasia, as well as conceptual criticism regarding the theory's application in the contemporary Middle East, suggest that this may be a case of African exceptionalism. This article moves these debates forward by posing a comprehensive, global set of tests on the democratizing effect of elections. We seek to establish the scope conditions of the argument geographically, temporally, and substantively. Although we find a correlation between reiterated multiparty elections and improvements in the liberal-democratic components of electoral regimes globally since 1900, the relationship is only substantial in the period since the onset of the third wave of democracy. Experiences with iterated multiparty elections have substantive importance for democratization in sub-Saharan Africa, the post-communist region, Latin America and the Caribbean, and Asia. For the Middle East and North Africa, the relationship is weaker and less robust. Finally, the results suggest that reiterated sequences of multiparty elections are associated with improvements to liberal and deliberative components of democracy more so than egalitarian components.